From stump to ship - Weiss, David; Ames, Alfred; Sheldon, Karan; Sample, Tim. (Orono, Me. : University of Maine at Orono, 1985)
This film survives as the best, most vivid and complete film record of the long log business. Remarkably detailed scenes, filmed year-round, are uniquely enhanced by the original script, written to be read with the silent footage of the 1930s. The soundtrack is brought to life by Tim Sample, narrator and renowned Maine humorist, in the role of the filmmaker, Alfred Ames
Consultants: David C. Smith, Edward Ives, Richard Judd, Jonathan Tankel.
A project of the University of Maine at Orono under a grant from the Maine Humanities Council and Champion International Corporation. Project director, Henry Nevison. Co-sponsored by Northeast Archives of Folklore and Oral History. Producers, Sheldon Weiss Productions.
Executive producer and project director, Harry Nevison ; graphics, Mike Mardose ; script editor, Karan Sheldon ; film editor, Harry Nevison, David Weiss ; music, Sandy Ives, Albert Pelletier, Billy Schubeck.
Tim Sample.
VHS.
Keywords: Logging -- Maine -- History; Lumbering -- Maine -- History